Macrophages regulate gastrointestinal motility through complement component 1q - Pendse, Mihir; De Selle, Haley; Vo, Nguyen; Quinn, Gabriella; Dende, Chaitanya; Li, Yun; Salinas, Cristine N; Srinivasan, Tarun; Propheter, Daniel C; Crofts, Alexander A; Koo, Eugene; Hassell, Brian; et al. (eLife, 2023)
Peristaltic movement of the intestine propels food down the length of the gastrointestinal tract to promote nutrient absorption. Interactions between intestinal macrophages and the enteric nervous system regulate gastrointestinal motility, yet we have an incomplete understanding of the molecular mediators of this crosstalk. Here, we identify complement component 1q (C1q) as a macrophage product that regulates gut motility. Macrophages were the predominant source of C1q in the mouse intestine and most extraintestinal tissues. Although C1q mediates the complement-mediated killing of bacteria in the bloodstream, we found that C1q was not essential for the immune defense of the intestine. Instead, C1q-expressing macrophages were located in the intestinal submucosal and myenteric plexuses where they were closely associated with enteric neurons and expressed surface markers characteristic of nerve-adjacent macrophages in other tissues. Mice with a macrophage-specific deletion of C1qa showed changes in enteric neuronal gene expression, increased neurogenic activity of peristalsis, and accelerated intestinal transit. Our findings identify C1q as a key regulator of gastrointestinal motility and provide enhanced insight into the crosstalk between macrophages and the enteric nervous system.
Keywords: enteric nervous system; macrophage; gut motility; intestine